If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -1) + 7 = 2x + 4(-1 + x) Reorder the terms: 6(-1 + x) + 7 = 2x + 4(-1 + x) (-1 * 6 + x * 6) + 7 = 2x + 4(-1 + x) (-6 + 6x) + 7 = 2x + 4(-1 + x) Reorder the terms: -6 + 7 + 6x = 2x + 4(-1 + x) Combine like terms: -6 + 7 = 1 1 + 6x = 2x + 4(-1 + x) 1 + 6x = 2x + (-1 * 4 + x * 4) 1 + 6x = 2x + (-4 + 4x) Reorder the terms: 1 + 6x = -4 + 2x + 4x Combine like terms: 2x + 4x = 6x 1 + 6x = -4 + 6x Add '-6x' to each side of the equation. 1 + 6x + -6x = -4 + 6x + -6x Combine like terms: 6x + -6x = 0 1 + 0 = -4 + 6x + -6x 1 = -4 + 6x + -6x Combine like terms: 6x + -6x = 0 1 = -4 + 0 1 = -4 Solving 1 = -4 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 0.16(y-7)+0.06y=0.20y-1.2 | | (-1/9)b=-12 | | 0.16(y-7)+0.064=0.20y-1.2 | | 4x-6=3+7x | | 1/20(h)=-6 | | 11x^2-122x+11=0 | | 17=-z+3 | | 14x-30=4x | | 2w^2-4w-1=0 | | 9.2x=22.08 | | 8x-3=23-5x | | 50+20=2u-7u | | 10x-16=6x | | -3p=-15 | | 685y-85=2y | | 20n+10n=4 | | 7a^2=-65-18 | | 2y=685+-85 | | 2x^2-5x-20=x^2-9x+1 | | 2.25-0.50x=0.375x+0.50 | | 9.9x=39.6 | | 2y+-685=85 | | n(n^2-7n-1)+7=0 | | -(-9x)=(-53) | | 5y+8=4y+1 | | 2c-21=3-4c | | 6x^2-22x+14=0 | | 6x^2=19x-15 | | 2y+685=85 | | n^2-7n-1=0 | | 6x^2+73x+12=0 | | 7x+2=8x |